Analysis of the Effect of Team Games Tournament (TGT) Type-Cooperative Learning Model on Students’ Interest and Learning Outcomes on the Concept of Viruses and Their Role in Life - Fitri, Siti Gia Syauqiyah; Pramesty, Putri Dian; Mulyati, Epi; Kholisoh, Kholisoh; Hajali, Siti Herlina (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
Education is a conscious and planned effort to create a learning atmosphere and learning process that enables students to actively develop their potential, including knowledge, capability, creativity, independence, and a noble character. This study aimed to analyze the effect of Team Games Tournament (TGT)-type cooperative learning on students' interest and learning outcomes regarding the concept of viruses and their role in life. The method employed in this research was a descriptive approach with a quantitative orientation. The research subject involves students of a high school in Serang, Banten. The study showed that the application of the TGT in the learning process significantly increased students' interest and their learning outcomes. Students were more active and competitive between learning groups. In conclusion, the TGT has a positive effect on students’ interest and learning outcomes.